Energy development and indigenous Mexican women: an implementation strategy approach in San Jose Villa de Allende, Mexico - Whaites, Hannah; Encinas-Oropesa, Adriana; Zarza-Delgado, Martha Patricia (Universidad Autonoma del Estado de Mexico, 2018)
Access to safe and sustainable energy is essential for human preservation and improvement of quality of life. Development is not possible without appropriate energy supplies. Arguably the biggest energy challenge of the 21st century is the health and wellbeing of 2.9 billion people globally who rely on burning biomass fuels in traditional stoves. This paper discusses the social and community level impact of using biofuels as an energy source in San Jose Villa de Allende, rural Mexico. Semi structured interviews were undertaken from indigenous women within the village. Picture evidence was also collected in order to identify the major energy problems of the community. The cooking stoves and fuels are identified as being the major contributors to time barriers and health issues for women. An implementation strategy for alternatives chimneys is suggested in order to develop policies for change and mitigate fuel poverty for an increased quality of life for rural Mexican women. The main discussion argues that cultural barriers and traditions are of foremost importance for policy making within the community.
Keywords: energy development; indigenous Mexican women